Investigating the differential microRNAs expression in young and aged Drosophila melanogaster following Flock House Virus infection - Amber Thibeaux; Max Yang Lu; Marshall Martin; Michael Rodwell; Victoria Faber; Lakbira Sheffield; Janna L. Fierst; Stanislava Chtarbanova (Virulence)
MicroRNAs (miRNAs) are small non-coding RNAs ~ 19–22 nt long that post-transcriptionally regulate their mRNA targets. In Drosophila melanogaster, the role of miRNAs has mostly been studied in regard to bacterial infection, yielding insights about their regulatory function in innate immunity. However, fewer studies have focused on viral infections, and importantly, how miRNAs modulate aging immune responses is not fully understood. Here, we performed small RNA-sequencing demonstrating that systemic Flock House Virus (FHV) infection of Oregon-R flies leads to differential microRNA expression and that this response differs with aging. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses identified cellular pathways and biological processes which may be regulated by dynamic expression of microRNAs during infection. For 17 candidate miRNAs, we tested Drosophila lines with in vivo miRNA knockdown for their survival of systemic FHV challenge. In response to infection, among miRNA knockdown lines, females consistently outlived males, and young flies generally outlived their aged counterparts. Furthermore, miRNA knockdown lines generally displayed increased susceptibility to viral infection in comparison to controls, particularly prominent among males. For one miRNA chosen for further study, miR-311, its dysregulation resulted in decreased survival independent of changes in viral load, suggesting a role in disease tolerance rather than resistance. Lastly, knockdown of the immune deficiency (imd) gene – a predicted target of miR-311 - was associated with improved survival of FHV. This work identifies changes in miRNA expression in the aging antiviral response and highlights one miRNA with a role in disease tolerance to FHV in Drosophila.